تكيف طلاب الجامعة مع البيئة الجامعية وعلاقتها بالتحصيل الدراسي في جامعة طرابلس . ليبيا . دراسة تطبيقية - Musbah Ali Swayah
The aim of this research is to reveal the relationship between adapting to the syllabus and the level of educational attainment among the students of the Tripoli University, Libya, as well as to identify the most important problems that hinder the students’ ability to adapt to the university courses. All that can be identified by answering, studying and analyzing the questions of this research. In order to describe and analyze the research problem, the researcher used the descriptive analytical method in the survey. As for the statistical method, SPSS and Amos programs are used to perform data analysis. The relative stratified sample was determined. The research sample consisted of 973 students, distributed among the faculties of the University of Tripoli. The results of the study showed a relationship between the variables of students’ adaptation the level of educational attainment. The research also found that there is no relationship between the university environment (as a mediator variable) and the educational attainment. However, it showed the relationship between the variables of adaptation, the university environment and the level of educational attainment. Through indirect relations and the impact of the active factor (academic specialization of the student) between the variables of research and the level of specialization, the results of the search proved a relationship between the variables of adaptation, environment and the educational attainment in favor of the specialization of humanities. In the light of the results of this research, the researcher recommends that officials and professors at the university help students, especially new ones to adapt to the syllabus. He also recommends the need to pay attention to curricula and syllabus by officials on university education and its institutions, and teachers in the development of curricula that are consistent with the local environment.